INTERNATIONALIZATION OF HIGHER EDUCATION AS FACTOR OF THE DEVELOPMENT OF UNIVERSITY - Nitenko, Olga V. (Educological discourse, 2015)
The article clarifies the definition of "internationalization of higher education"; gives some statistics of the Organization for Economic Cooperation and Development and UNESCO Institute for Statistics about mobile international students and foreign students in the world; shows the actual statistics obtained of Centre for the Study of Society about mobility of Ukrainian students abroad and mobility of foreign students who study in Ukrainian universities. The article shows the necessity of teacher mobility as part of the internationalization of higher education. The article marks recent internationalization trends, which are observed worldwide; lists the positive aspects of internationalization of higher education and elements of the culture of the University, which must be developed in terms of internationalization.